Tra territorio e città (2014)
By summarising some selected bachelor and master's degree theses, the volume offers an overview of the study activities conducted within the Degree courses in Planning of the University of Florence, Empoli Campus. The different sections constituting the work highlight a multi-scale and multidisciplinary work methodology, which feeds on an approach mainly based on the importance given to the value of places and of specific territorial contexts. The result is an original picture of contributions, representing a potentially innovative way for the comparison of territorial and urban studies with the various operational dilemmas which arise at the intersection between the drafting of policies, the construction of long-lasting territorial projects and the local development guidelines.